2016
DOI: 10.1371/journal.pone.0168595
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Bacterial Biofilms to Electrical Current Leads to Cell Death Mediated in Part by Reactive Oxygen Species

Abstract: Bacterial biofilms may form on indwelling medical devices such as prosthetic joints, heart valves and catheters, causing challenging-to-treat infections. We have previously described the ‘electricidal effect’, in which bacterial biofilms are decreased following exposure to direct electrical current. Herein, we sought to determine if the decreased bacterial quantities are due to detachment of biofilms or cell death and to investigate the role that reactive oxygen species (ROS) play in the observed effect. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 41 publications
1
23
0
1
Order By: Relevance
“…A gold cathode with carbon and platinum anodes were reported to be the most effective against the urinary tract planktonic pathogens E. coli and P. mirabilis , while silver, nickel, or copper electrodes corroded to the point of breaking during experiments 17 . In another study, the authors showed application of direct current through platinum electrodes resulted in an increase in the production of reactive oxygen species (ROS) responsible for killing of S. aureus , S. epidermidis and P. aeruginosa biofilms 45 . It is certainly possible that other cidal agents besides HOCl may be active in the PA biofilm remediation observed in our results.…”
Section: Discussionmentioning
confidence: 99%
“…A gold cathode with carbon and platinum anodes were reported to be the most effective against the urinary tract planktonic pathogens E. coli and P. mirabilis , while silver, nickel, or copper electrodes corroded to the point of breaking during experiments 17 . In another study, the authors showed application of direct current through platinum electrodes resulted in an increase in the production of reactive oxygen species (ROS) responsible for killing of S. aureus , S. epidermidis and P. aeruginosa biofilms 45 . It is certainly possible that other cidal agents besides HOCl may be active in the PA biofilm remediation observed in our results.…”
Section: Discussionmentioning
confidence: 99%
“…This bioelectric effect is not fully understood yet, although several factors potentially contributing to the increased efficacy have been described. The oxygen and reactive oxygen species (ROS) that are produced duringthe electrolysis of water contribute to the increased susceptibility [ 121 , 122 ]. In addition, the electric current reduces the antibiotic binding capabilities of the matrix and increases permeability of biofilm cells (electroporation), leading to an increased antibiotic uptake in the cells [ 122 ].…”
Section: Biofilm Dispersion: the Two Mechanismsmentioning
confidence: 99%
“…The oxygen and reactive oxygen species (ROS) that are produced duringthe electrolysis of water contribute to the increased susceptibility [ 121 , 122 ]. In addition, the electric current reduces the antibiotic binding capabilities of the matrix and increases permeability of biofilm cells (electroporation), leading to an increased antibiotic uptake in the cells [ 122 ]. The effect of a low electric current has also been evaluated in vivo using rabbits [ 123 ].…”
Section: Biofilm Dispersion: the Two Mechanismsmentioning
confidence: 99%
“…To effectively eradicate biofilms, many anti‐biofilm approaches have been developed, mainly mechanical removal of biofilms, which includes electricity and sonication, and chemotherapy, which is the focus of this review. Novel drug candidates must be developed for effective anti‐biofilm therapy of chronic infections in humans.…”
Section: Development Of Anti‐biofilm Chemotherapymentioning
confidence: 99%